Knowledge transfer strategies and practices for higher education institutions. Issue 2 (2nd April 2020) - Cheng, Eric C.K.
Abstract : Purpose: This study aims to identify effective strategies and practices for higher education institutions (HEIs) to enhance their knowledge recipients' knowledge absorptive capacity. Design/methodology/approach: Questionnaire surveys and interviews were conducted to examine the effectiveness of a knowledge transfer (KT) project and these were administered by HEIs in Hong Kong. Pre- and post-test questionnaire surveys with t -tests were used to evaluate changes in the knowledge absorptive capacity of 1, 014 participants from 20 schools. Qualitative interviews were conducted to investigate school leaders' perception of the effectiveness of the KT strategies. Findings: Results revealed significant differences between the pre- and post-tests in all the elements of absorptive capacity. The processes of knowledge acquisition, contextualisation, internalisation and externalisation in a closed-loop mechanism were identified as effective KT strategies. Conducting training programmes, workshops, consultations, work-based studies and presentation seminars were found to be effective KT practices to support the recipients in acquiring, contextualising, internalising and externalising knowledge. Practical implications: HEIs should provide consultative support to recipients by conducting work-based studies and presentations to enhance their knowledge absorptive capacities. Originality/value: This study contributes empirical evidence to validate the application of Liyanage et al. 's (2009) KT model to HEIs' KT model for the purpose of designing KT activities and enhancing the absorption capacities of the recipients. This research contributes an empirical closed-loop KT model, effective KT strategies and practices for HEIs to support their knowledge recipients so that they can internalise the acquired knowledge.